STRATEGI PEMBANGUNAN BERWAWASAN LINGKUNGAN DI DISTRIK MUARA TAMI - Henny Rosita Mantundoij; Janviter Manalu; Harmonis Rante (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2021)
In the framework of formulating policies, plans and / or programs, KLHS can be used as a tool to prepare alternative improvements to policies, plans and programs so that unexpected environmental impacts and risks can be minimized. In general, the environment is defined as all objects, conditions, conditions and influences that exist in the room we live in, and affect living things, including human life.In the provisions of article 1 paragraph 3 of Law Number 32 of 2009 concerning Environmental Protection and Management, it is stated that sustainable development is a conscious and planned effort that integrates environmental, social and economic aspects into a development strategy to ensure environmental integrity and safety, capability. , welfare, and quality of life of present and future generations. Managing natural resources, both renewable and non-renewable through the application of environmentally friendly technology by taking into account their carrying capacity and capacity. The direction of regional development in the field of natural resources and the environment is basically an effort to make the best use of natural resources for the prosperity of the people by taking into account the preservation of the function and balance of the environment, sustainable development, policies that are set according to their respective functions. The target of this program is to increase the control of environmental impacts and environmental quality in line with the increase in the quality of nature preservation and the number of city residents who have concern and awareness of the importance of the environment.